The Impact of Parent and Community Support on Primary Schools’ Pupils Academic Achievement in Siaya and Kisumu Counties, Kenya - Oduor, Onyango D. (Machakos University, 2018)
The performance of primary school pupils in the Kenya Certificate of Primary Education (KCPE) examinations in Siaya and Kisumu Counties has been unsatisfactory over the years. Most of the candidates obtain at least average and below average scores in the annual examination. This has been a cause for worry among parents, teachers and the community. The purpose of the study was to investigate teachers’ perceptions of the influence of parents and community factors on primary school pupils’ academic achievement in Siaya and Kisumu counties. The objective of the study was to:establish teachers’ perceptions on whether the parent and community support determine primary schools pupils’ academic achievement. The study was guided by the Transaction Theory of Teaching/Learning and General Systems Theory. The study wasconductedin the counties of Siaya and Kisumu. The study employed the mixed methods approach and was conducted using descriptive explanatory survey design. The instruments used to collect data included questionnaires and interview guide. The sample was selected using stratified random sampling. Data was collected from 136 schools where 136 head teachers and 493 teachers were respondents. The researcher interviewed 36 teachers. The unit of analysis was primary school teachers. Descriptive statistics, such as measures of central tendency, counts and percentages were used to analyze the data. The study found that parenting style, social gatherings such as discos and pupils’ absenteeisminfluenced academic achievement. It was found that since the school is a system, it has sub-systems such as parent community. These sub-systems interacted and were dependent on each other. As such, problems in one variable affected the other. For example, the post-election violence of 2008 which took place in some parts of the study area affected pupils’ KCPE achievement.
Keywords: Academic achievement